Association of zein nanoparticles withbotanical compounds for effective pestcontrol systems - Oliveira, Jhones L. De [UNESP]; Ramos Campos, Estefania Vangelie [UNESP]; Germano-Costa, Taís; Lima, Renata; Della Vechia, Jaqueline Franciosi [UNESP]; Soares, Sidneia Terezinha; Andrade, Daniel Junior De [UNESP]; Gonçalves, Kelly Cristina [UNESP]; Nascimento, Joacir do [UNESP]; Polanczyk, Ricardo Antonio [UNESP]; Fraceto, Leonardo Fernandes [UNESP] (Wiley, 2019)
BACKGROUND: Botanical compounds from plant species are known to have pesticidal activity and have been used in integratedpest management programs. The varied spectrum of the pesticidal action of these compounds can also avoid selection ofresistance in pest populations. In this study, mixtures of the botanical compounds geraniol, eugenol and cinnamaldehyde wereencapsulated in zein nanoparticles to improve their stability and efficiency. Biological effects of the nano-scale formulations ofthe botanical compounds were evaluated against two agricultural pests: the two-spotted spider mite (Tetranychus ur ticae)andthe soybean looper (Chrysodeixis includes).RESULTS: The formulations were stable over time (120 days) with a high encapsulation efficiency (>90%). Nanoencapsulationalso provided protection against degradation of the compounds during storage and led to a decrease in toxicity to non-targetorganisms. The release of the compounds (especially eugenol and cinnamaldehyde) from the nanoparticles was directlyinfluenced by temperature, and the main mechanism of release was through a diffusion-based process. Nanoencapsulatedcompounds also showed superior efficiency compared to the emulsified compounds in terms of repellency and insecticidalactivity.CONCLUSION: The findings of this study indicate that the convergence of botanical compounds with nano-scale formulation hasthe potential to improve efficacy for their sustainable use in integrated pest management in agriculture.
Keywords: Botanical pesticides; Nano-scale; Environmentally friendly formulations